An oxygen-vacancy rich 3D novel hierarchical MoS2/BiOI/AgI ternary nanocomposite: enhanced photocatalytic activity through photogenerated electron shuttling in a Z-scheme manner. Issue 36 (26th August 2016) - Jahurul Islam, M.; Amaranatha Reddy, D.; Han, Noh Soo; Choi, Jiha; Song, Jae Kyu; Kim, Tae Kyu
Abstract : Herein, we propose the photocatalytic mechanism, involving a Z-scheme and oxygen vacancy states, for the MoS2 /BiOI/AgI nanocomposite. Abstract : An oxygen-vacancy rich, bismuth oxyiodide-based Z-scheme 3D hierarchical MoS2 /BiOI/AgI ternary nanocomposite photocatalyst was fabricated using a simple precipitation process in ethylene glycol and water. The presence of oxygen-vacancies in BiOI and the two-dimensional nature of molybdenum disulfides in the composite prolongs the charge carrier lifetime through a Z-scheme system and enhances the performance of the photocatalyst for the degradation of rhodamine B. On the basis of efficient separation of photoexcited electron–hole pairs, a mechanism is proposed whereby MoS2 and oxygen vacancy states increase charge carrier lifetimes and improve the photocatalytic activity. The Z-scheme mechanism of the photocatalysis is consistent with the results of static and time-resolved photoluminescence, scavenging, and terephthalic acid photoluminescence experiments. Among the as-synthesized photocatalysts, the one containing 2 wt% of MoS2 in a composite of MoS2 /BiOI/AgI exhibited the highest photocatalytic activity towards rhodamine B degradation, and its activity was 7 and 16 times higher than that of BiOI/AgI and BiOI, respectively. Degradation of phenol, the colorless model pollutant, was studied to confirm the visible-light photocatalytic performance of the MoS2 /BiOI/AgI composite. This easily fabricated Z-scheme based MoS2 /BiOI/AgI composite exhibits promising photocatalytic activity and will be useful for potential applications in energy and environmental areas.